The Effect of Parents' Income and Learning Achievement on Students' Interest in Continuing to Higher Education at SMA Negeri 1 Bunut - Talitha Syaikha Ariba; Suarman Suarman; R. M. Riadi (CV. Rayyan Dwi Bharata, 2024)
This study aims to determine the effect of parental income and learning achievement on students' interest in continuing to higher education. The background of this research is that students' interest in continuing to higher education is still low. This study was included in survey research with 61 students as respondents using a proportional random sampling technique. Data were obtained by means of questionnaires and documentation, then analyzed using multiple linear regression analysis, where previously carried out normality tests, linearity tests, and multicollinearity tests. The results of the study showed that most of the respondents had an interest in continuing to tertiary education, including the moderate category. Of the two influencing factors, namely the level of parental income and learning achievement, it turns out that both partially and simultaneously have an effect on students' interest in continuing to tertiary education. Thus the interest of students to go to college is not only determined by the size of the parent's income but also the learning achievement factor also determines students to go on to college.